Losing the Plot A Nutcracker troika - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2005)
A Nutcracker troika. Choreographers should beware of patronising attempts to pass ballet off as an extension of kids' culture. Popstar automata, breakdancing robots and the like cut no ice. PALABRAS CLAVE: The Nutcracker, narrative structure, Mark Morris.